2021
DOI: 10.3389/fmicb.2021.679805
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antibiotic Resistance Genes, Environmental Factors, and Microbial Community From Aquaculture Farms in Five Provinces, China

Abstract: The excessive use of antibiotics speeds up the dissemination and aggregation of antibiotic resistance genes (ARGs) in the environment. The ARGs have been regarded as a contaminant of serious environmental threats on a global scale. The constant increase in aquaculture production has led to extensive use of antibiotics as a means to prevent and treat bacterial infections; there is a universal concern about the environmental risk of ARGs in the aquaculture environment. In this study, a survey was conducted to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Although pipA and spiC are responsible for Salmonella virulence, they were significantly poor predictors of each other in this study, having displayed significant negative correlations as similarly documented by others (Gao & Tikekar, 2023;Uchiya & Nikai, 2008). Partly like our findings is the report of a previous empirical evaluation of environmental samples of aquaculture farms where antimicrobials are used, and positive correlations were established between sul1, sul2, sul3, qnrS, and other genes (Cheng et al, 2021). Furthermore, Pavon et al…”
Section: Discussionsupporting
confidence: 86%
“…Although pipA and spiC are responsible for Salmonella virulence, they were significantly poor predictors of each other in this study, having displayed significant negative correlations as similarly documented by others (Gao & Tikekar, 2023;Uchiya & Nikai, 2008). Partly like our findings is the report of a previous empirical evaluation of environmental samples of aquaculture farms where antimicrobials are used, and positive correlations were established between sul1, sul2, sul3, qnrS, and other genes (Cheng et al, 2021). Furthermore, Pavon et al…”
Section: Discussionsupporting
confidence: 86%
“…The common antibiotic resistance genes recovered in aquaculture systems include sul1 , sul2 , bla CMY , bla OXA , qnrS , tetW , tetQ , tetM , and intl1 . Some of these genes have been recommended for standard surveillance of ARGs in water systems and aquaculture [ 153 ]. Different metagenomics approaches have revealed that certain ARGs are shared and exchanged between the gut microbiomes of humans and animals [ 154 ].…”
Section: Antibiotic Resistance Genes and One Healthmentioning
confidence: 99%
“…Barcoding uses species-specific primers to detect DNA fragments of a single species within a sample [141], while metabarcoding uses universal primers to detect millions of DNA fragments from various species [142]. This technique has been commonly used in aquatic ecosystems to assess biodiversity, such as in fish, amphibians [143], and bacterial antibiotic resistance genes (ARGs) [144]. Terrestrial ecosystems have also been assessed using eDNA, including terrestrial vertebrate diversity and global plant diversity using soil eDNA and pollen DNA [145,146].…”
Section: Application Of Edna Technology On Bioaerosol Studymentioning
confidence: 99%